Greening the Philippine employment projections model: New estimates and policy options - Michael Ralph M. Abrigo; Danica Aisa P. Ortiz; Aniceto C. Orbeta; Gilberto M. Llanto (Philippine Institute for Development Studies (PIDS), 2021)
Climate change causes a vast magnitude of impacts that cut across boundaries and spill over time. It results in various, interrelated effects on important aspects of society. Direct and indirect effects of climate change touch on, for instance, health (e.g., Watts et al. 2015) and on labor (e.g., Kjellstrom et al. 2009; International Labor Organization 2018). Unfortunately, developing countries, which are the least contributors to climate change, are more exposed to environmental risks. According to the Global Climate Risk Index 2017, the Philippines, is in the top ten countries greatly affected by extreme weather events over the last two decades. In response to these challenges and risks, the country has been actively participating in international efforts to address this global concern. Locally, various policies have been enacted to create a progressive landscape for environmental protection, and disaster risk mitigation and response. Adding to these mitigation responses is the Green Jobs Act of 2016, which aims to encourage the creation and nurturing of green jobs along with the country's transition towards a more environmentally sustainable economy. [...]
Keywords: 330; green jobs; environment; labor market; disaster risk mitigation; climate change